Corpulence is the crucial factor: Association of testosterone and/or obesity with prostate cancer stage. (27th May 2014) - Jentzmik, Florian; Schnoeller, Thomas J; Cronauer, Marcus V; Steinestel, Julie; Steffens, Sandra; Zengerling, Friedemann; Al Ghazal, Andreas; Schrader, Mark G; Steinestel, Konrad; Schrader, Andres J
<x xml:space="preserve">Abstract</x> Objectives To evaluate whether low testosterone levels or obesity, or both, are directly associated with tumor stage/grade in patients with clinically localized prostate cancer. Methods Preoperative androgen serum levels (total and free testosterone), sex hormone‐binding globulin, body mass index and waist circumference were assessed in 510 consecutive European Caucasian men treated with radical prostatectomy. Hormone levels and body mass index/waist circumference were correlated with patient‐ and tumor‐specific characteristics using multivariable logistic regression analysis. Results Even though we confirmed an inverse correlation between bodyweight and testosterone levels, only overweight – but not low testosterone – was associated with advanced disease and poor differentiation of prostate cancer. Using multivariate analyses, both body mass index ≥30 kg/m2 and waist circumference >110 cm were associated with high‐grade disease (Gleason score ≥8). A waist circumference >110 cm also correlated significantly with lymph node metastasis. Conclusions This is the first study showing that obesity, but not low serum testosterone levels, is significantly associated with high grade and metastatic disease in men diagnosed with clinically localized prostate cancer. The present findings suggest that low androgen levels at diagnosis, which used to be held responsible for the development of aggressive prostate cancer, is only an epiphenomenon of obesity rather than the cause of prostate cancer development and/or progression.